Identification Of Marine Debris By Focusing The Study Of Clean Coast Index On Karang Ria Tuminting Beach - Poluan, Tirza I. A.; Sangari, Joudy R. R.; Tilaar, Ferdinand Frans; Lumingas, Lawrence J. L.; Pelle, Wilmy E.; Lasabuda, Ridwan (Jurnal Ilmiah Platax, 2023)
Marine debris is rapidly gaining worldwide recognition as a major anthropogenic threat to global ocean ecosystems and produces a wide range of negative environmental, economic, safety, health and cultural impacts (UNEP, 2009). East Asia is the region with the fastest growing waste production in the world. Indonesia is in second position after China which produces the most waste in the world (Jambeck et al, 2015). The Beach Hygiene Index is a scaled index in a “Clean Coast” program launched by the Israeli ministry in an effort to solve the problem of littering on Israel's beaches. This index can be used as an indicator of pollution in a marine tourism area. The purpose of this study was to identify types of marine debris in the coastal waters of Karang Ria Tuminting and determine the value of the Clean Coast Index as an indicator of pollution. The collected data was then processed and statistically analyzed using Excel, Orange and SPSS software. Sampling was done by adapting the Shoreline Survey Methodology. approximately 1 month and made 2 direct observations, the plastic and rubber waste categories were found as the most common categories with the first observation being 73.4% and the second observation being 10.1%. The activities of the surrounding community are the main factors causing the abundance of marine debris around the coastal areas. The index value obtained is 39.5 with a total of 395 waste in various categories as stated by NOAA (2016). Keywords: Marine debris, Index, Identification, Category ABSTRAK Sampah laut dengan cepat mendapatkan pengakuan dunia sebagai ancaman antropogenik utama bagi ekosistem lautan global dan menghasilkan berbagai macam dampak negatif lingkungan, ekonomi, keselamatan, kesehatan, dan budaya (UNEP, 2009). Asia Timur adalah wilayah dengan pertumbuhan produksi sampah tercepat di dunia. Indonesia berada pada posisi kedua setelah China yang memproduksi sampah terbanyak di dunia (Jambeck et al, 2015). Indeks Kebersihan Pantai adalah skala indeks dalam suatu program “Clean Coast” yang diluncurkan kementerian Israel dalam upaya untuk memecahkan permasalahan sampah di pantai-pantai Israel. Indeks ini dapat digunakan sebagai indikator polusi pada suatu kawasan wisata bahari. Tujuan penelitian ini untuk mengidentifikasi jenis sampah laut di perairan pantai Karang Ria Tuminting dan menentukan nilai Indeks Kebersihan Pantai (Clean Coast Index) sebagai indikator polusi. Data yang dikumpulkan kemudian diolah dan dianalisis secara statistik dengan menggunakan perangkat lunak Excel, Orange dan SPSS. Pengambilan sampel dilakukan dengan mengadaptasi metode Shoreline Survey Methodology. Pengamatan dilaksanakan kurang lebih 1 bulan dan dilakukan 2 kali pengamatan langsung, diperoleh kategori sampah plastik dan karet sebagai kategori yang paling banyak ditemukan dengan komposisi jumlah pada pengamatan pertama sebesar 73.4% dan pengamatan kedua sebanyak 10.1%. aktivitas masyarakat sekitar menjadi faktor utama penyebab berlimpahnya sampah laut di sekitar wilayah pesisir. Nilai indeks yang diperoleh yaitu sebanyak 39,5 dengan jumlah total 395 sampah dengan berbagai kategori sesuai dengan yang dikemukakan oleh NOAA (2016). Kata kunci : Sampah laut, Indeks, Identifikasi, Kategori